(untitled) (Journal of Contemporary Philology, 2019)
This paper looks at indeclinable words or expressions at discourse level, treating them as upgraded elements of propositional meaning and modifiers of textual meaning. Given their function, we use the polish term modulantsand apply the classification of these discourse elements as suggested by Grochowski. The term is accepted in Polish translation science as being common to units of text whose categorical-grammatical nature is diverse: it can include traditional particulates, genetic prepositions, some pronouns, often pronouns, evaluative or affective char-acter, and even and intentional conjunctions, as well as whole language phrases with an established morphological structure. The analysis is based on examples from Polish literary works and their equivalents in the Macedonian translation, i.e., on the differences in translation based on the semantic nuances introduced by the modulators. Language equivalents do not always perform the same function, thereby fitting the additional nuances of meaning and causing differences between the original and the translation. Those differences arise either through the use of functionally misfit equivalents or through omitting these so called “facultative” elements, following the wrongly traditional linguistic understanding of their use-fulness for the text. The analysis aims to show exactly the opposite–that is, that they are important for the text and, in particular, for the translation.